2022
DOI: 10.3390/horticulturae8050388
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Girdling and Foliar Fertilization with K on Physicochemical Parameters, Phenolic and Volatile Composition in ‘Hanxiangmi’ Table Grape

Abstract: Aroma is one of the most important indicators of grape quality. Girdling and foliar fertilization with K (K2O) are common agronomic practices applied to improve berry quality in grape production. However, little is known about its effect on the accumulation and biosynthesis of the entire aromatic profile. Our study was aimed to explore the influences of girdling and foliar fertilization with K (alone or in combination) on the general properties, phenolic composition, volatile free aroma compounds, spatial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The content of total anthocyanins in red grape berries was determined using the pH differential method with dimethyl anthocyanin (mg/kg) [ 13 ]. The flavonoid content was determined using the sodium nitrite-aluminum nitrate method [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of total anthocyanins in red grape berries was determined using the pH differential method with dimethyl anthocyanin (mg/kg) [ 13 ]. The flavonoid content was determined using the sodium nitrite-aluminum nitrate method [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that terpenes, C13 isoprene, methoxypyrazine, C6-alcohol, aldehydes, esters, and mercaptans are among the most important compounds that contribute to the aroma of grapes [ 12 ]. Among these compounds, terpenes and esters provide floral and fruity characteristics to grapes, while alcohols and C6 aldehydes contribute to a herbaceous flavor [ 13 ]. Table grapes are classified into groups depending on the type of aroma [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The experiments were performed with 5-year-old 'Yinhong' table grape vines between May and July 2021 in an irrigated vineyard at Cixi, Zhejiang, China (30 • 16 6.59 N, 121 • 25 2.18 E). The physical and chemical properties of the soil were as follows: soil type, clayey soil; pH, 6.4; soil depth, 102 cm; total organic matter content, 25 g•kg −1 ; basic nitrogen, 202 mg•kg −1 ; available phosphorus, 35 mg•kg −1 ; available potassium, 114 mg•kg −1 ; soil bulk density, 112.3 g•cm −1 ; and groundwater level, 55-60 cm [37]. The soil is a typical marine sedimentary plain soil, with a deep and sparse soil layer and good permeability.…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%
“…and Mpelasoka et al 19 . P and K participate in the transport of sugar and acid, the response of hormones, and the synthesis of polyphenols related to color and aroma 23,24 . Moreover, exogenous P and K fertilizers can promote the accumulation of soluble solids and anthocyanin in grapes 24,25 …”
Section: Introductionmentioning
confidence: 99%
“…16,21,22 The role of P and K nutrition on yields and fruit quality in grapevines has been reviewed by Brunetto et al 11 and Mpelasoka et al 19 P and K participate in the transport of sugar and acid, the response of hormones, and the synthesis of polyphenols related to color and aroma. 23,24 Moreover, exogenous P and K fertilizers can promote the accumulation of soluble solids and anthocyanin in grapes. 24,25 Traditionally, most plants mainly take up P and K applied to the soil through the roots.…”
Section: Introductionmentioning
confidence: 99%